2017
DOI: 10.1073/pnas.1611595114
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of catalysis, E2 recognition, and autoinhibition for the IpaH family of bacterial E3 ubiquitin ligases

Abstract: IpaH enzymes are secreted bacterial effectors that function within host cells as E3 ubiquitin (Ub) ligases. Catalytic activity is imparted by a conserved novel E3 ligase (NEL) domain that is unique to Gram-negative pathogens and whose activity is repressed by a flanking substrate-binding leucine-rich repeat (LRR) domain when substrate is absent. How the NEL domain catalyzes the conjugation of Ub onto substrates, recognizes host E2s, and maintains its autoinhibited state remain poorly understood. Here we used m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 50 publications
3
34
1
Order By: Relevance
“…2). The LRR domain is connected to the NEL domain through a flexible linker and inhibits its ubiquitin ligase activity in the absence of substrate proteins (Chou et al, 2012;Quezada et al, 2009;Keszei and Sicheri, 2017). Removal of the LRR domain from SspH1, SspH2, SlrP or IpaH9.8 increases their E3 ligase activity (Quezada et al, 2009;Chou et al, 2012;Zouhir et al, 2014).…”
Section: Novel E3 Ligasesmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The LRR domain is connected to the NEL domain through a flexible linker and inhibits its ubiquitin ligase activity in the absence of substrate proteins (Chou et al, 2012;Quezada et al, 2009;Keszei and Sicheri, 2017). Removal of the LRR domain from SspH1, SspH2, SlrP or IpaH9.8 increases their E3 ligase activity (Quezada et al, 2009;Chou et al, 2012;Zouhir et al, 2014).…”
Section: Novel E3 Ligasesmentioning
confidence: 99%
“…A structural study of SspH1 showed that the binding of the host protein kinase N1 (PKN1) to the LRR domain releases its inhibitory effect on the NEL domain, which promotes the ubiquitylation and degradation of PKN1, and leads to the attenuation of the androgen response (Haraga and Miller, 2006;Keszei et al, 2014). Site-directed mutagenesis suggests that the LRR domain inhibits the activity of NELs not by preventing the catalytic cysteine from forming an intermediate with ubiquitin, but by selectively blocking the transfer of ubiquitin onto substrate proteins (Keszei and Sicheri, 2017).…”
Section: Novel E3 Ligasesmentioning
confidence: 99%
“…Most previous measurements of ubiquitination rates relied on quantification of protein bands from Western blots (e.g. [21][22][23][24]). While reliable, SDS-PAGE and antibody detection steps are time-consuming and expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Despite structural differences, SspH/IpaH E3s share important functional similarities with their eukaryotic HECT counterparts. Like HECT E3s, SspH/IpaH E3s form an E3ϳUb intermediate, use specific host E2ϳUbs, and target specific host proteins (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Although the structure of the SspH1 E3 domain has not yet been solved, those of several E3s, including the closely related SspH2 from Salmonella (77.6% identical in the E3 domain), are available. In addition, several studies have shown that SspH/IpaH E3s use E2ϳUbs from the Ube2D (UbcH5) family as a source of activated Ub (12)(13)(14)(15)(16)20). Thus, SspH1 is a structurally tractable system for investigating protein interactions and domain motions that occur during substrate ubiquitylation.…”
mentioning
confidence: 99%